Hygienic Characteristics Of Harmful Factors In The Production Of Construction Materials - Tashpulatova Munisa Nigmanjanovna (Genius Journals, 2025)
The article presents the results of a study of the features of the technological process and hygienic assessment of harmful factors in the production of ceramic-faced tiles.
Keywords: manufacturing enterprise; working conditions; dust